PAX8 and MECOM are interaction partners driving ovarian cancer - Melusine Bleu (Nature Portfolio, 2021)
Lineage-restricted transcription factor PAX8 is oncogenic in ovarian cancer cells. Here the authors show that PAX8 interacts and recruits a splice variant of the MECOM locus PRDM3 to control the gene expression module involved in adhesion and extracellular matrix, and consequently promotes ovarian tumorigenesis.